Perceptions of Students Regarding Changes in LMS of AIOU, Islamabad, Pakistan - Asma, Shahzadi; Mahar, Muhammad Ijaz; Abida, Yousaf; Ullah, Khan; Norina, Jabeen (2022)
Information Technology (IT) has long been a part of daily life in educational institutions around the world, including Pakistan. A learning management system (LMS) is designed to assist students by facilitating learning and communication. In recent years, LMS has gained popularity among students as a method of acquiring knowledge through electronic media. The use of computers and an understanding of information technology are required for this. The current study sought to learn more about how students at AIOU Islamabad, Pakistan, perceive the changes in learning management systems by distributing a questionnaire consisting of a few questions related to LMS. Majority of the respondents involved in the study were females (51.67%) while 48.32% were males. The respondents with Bachelor, Masters, MS/M.Phil, and Ph.D. levels of degree were 31.62%, 30.07%, 27.20%, and 11.13%, respectively. It is concluded that the majority of participants (male and female) had no internet facility which is a very important part of LMS. Syllabus and course materials were the frequently used tools of LMS in the study area. LMS can be a highly effective learning tool when they are designed to be scalable and able to adapt to the needs of the University. According to research, electronic Moodle-based LMSs may be more effective than traditional face-to-face teaching, resulting in learning outcomes that equal or exceed those of face-to-face teaching. Students face difficulties using Microsoft teams because they are not well aware of its functionality. It was recommended that proper training regarding the usage of the AIOU Aaghi LMS Portal should be provided for the provision of efficient learning environment.